2017
DOI: 10.1002/phar.1929
|View full text |Cite
|
Sign up to set email alerts
|

Benzalkonium Chloride: A Bronchoconstricting Preservative in Continuous Albuterol Nebulizer Solutions

Abstract: For convenience, many pediatric hospitals are preparing solutions for continuous nebulized albuterol using the 0.5% 20-ml multidose albuterol dropper bottle. This product contains benzalkonium chloride (BAC) that, by itself, produces bronchospasm that is dose dependent and cumulative. The bronchoconstrictive effects of BAC are greater in patients with more severe airway obstruction and increased airway responsiveness. Use of BAC-containing albuterol during severe acute asthma exacerbations may antagonize the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Other studies have suggested that β2 -adrenoceptor agonists induced bronchospasm may be related to inhalant excipients (propellants and surfactants), preservatives (benzalkonium bromide), osmotic pressure, and/or pH [1,8] . Benzalkonium bromide has been mentioned several times in preservatives [13][14][15] , and ededidine disodium has also been reported [16] .In this case, the patient used terbutaline sulfate nebulizate, which does not contain preservatives and excipients, but its excipients contain ededine disodium [1] , which may be the cause of bronchospasm. In addition, osmotic pressure of nebulized uids can cause bronchoconstriction, hypertonic buffers have been shown to cause the release of histamine from normal human basophils and mast lung cells, and both hypotonic or hypertonic saline solutions can induce bronchoconstriction [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that β2 -adrenoceptor agonists induced bronchospasm may be related to inhalant excipients (propellants and surfactants), preservatives (benzalkonium bromide), osmotic pressure, and/or pH [1,8] . Benzalkonium bromide has been mentioned several times in preservatives [13][14][15] , and ededidine disodium has also been reported [16] .In this case, the patient used terbutaline sulfate nebulizate, which does not contain preservatives and excipients, but its excipients contain ededine disodium [1] , which may be the cause of bronchospasm. In addition, osmotic pressure of nebulized uids can cause bronchoconstriction, hypertonic buffers have been shown to cause the release of histamine from normal human basophils and mast lung cells, and both hypotonic or hypertonic saline solutions can induce bronchoconstriction [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Although there is substantial evidence that BAC induces bronchospasm in clinical pharmacology studies of patients with stable asthma 7 and there are a few recent case reports regarding difficulty weaning children exposed to BAC from continuous nebulized albuterol, 8,9 this is the first study comparing the clinical outcomes of specifically pediatric patients with asthma exacerbation receiving continuous albuterol nebulization with an albuterol formulation containing BAC compared to a formulation that is preservative free. Previous studies have demonstrated that the effect of BAC nebulized in the airways of patients with stable asthma was dose dependent, cumulative, and more pronounced in patients with greater baseline airway reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of paradoxical bronchospasm during nebulization treatment for asthma have been reported and attributed to BAC [83, 84], prompting calls for its removal from the available formulations [85, 86]. On the other hand, paradoxical bronchospasm has been documented even in response to bronchodilators themselves [87–89] as well as other compounds added to nebulization solution [90, 91], and even biologically inactive substances such as saline and distilled water [92, 93], underscoring the limited value of anecdotal evidence especially with respect to common multifactorial conditions such as asthma.…”
Section: Discussionmentioning
confidence: 99%